Patho-morphological changes in experimentally induced cadmium chloride toxicity in wistar rats - Navdeep Kour; Shafiqur Rahman; Shagufta Azmi; Sahil Dutta; Heena Wani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was undertaken to elucidate the pathomorphological changes in various visceral and immune organs of Wistar rats administered with cadmium chloride @ 100, 250 and 500 ppm, respectively in drinking water in groups II, III and IV for 12th weeks while group I rats served as control. Six randomly selected rats from each group were sacrificed at 6th and 12th week post exposure (PE). Grossly, liver and kidneys were pale and enlarged; spleen and thymus was atrophic and meningeal blood vessels were congested in toxin administered rats. Relative weights of liver, kidneys, lungs, heart and brain were significantly increased whereas relative weights of spleen and thymus declined significantly in treatment group rats. Histopathological examination revealed vacuolar degeneration, necrosis, MNC’s infiltration, engorgement of blood vessel and oedema. The main target organs were found to be liver and kidneys but spleen, thymus, lungs, heart and brain were also affected. The intensity and distribution of lesions were more severe in group IV rats sacrificed at 12th week PE as compared to other groups in dose and duration dependent manner. Hence, the results of the present study indicated that cadmium chloride at dose rate of 100, 250 and 500 ppm in drinking water for 12th weeks caused severe damage to liver, kidneys, lungs, spleen, thymus and brain being hepatotoxic, nephrotoxic, immunotoxic and neurotoxic.